Analysis and assessment of the organisation’s internal control risks - E. A. Kirovа; T. V. Perminova (Вестник университета)
Risk management is an important part of an organisation’s internal controls and needs to be adjusted in response to changes in the external environment. In this article the problem of risk prevention and loss reduction in the organisation’s internal control system has been solved in the current environment. The existing risks were analysed and described, classification of external and internal risks was developed and methodology of risk tolerance and possibility of diversification was proposed. It was proved that the proposed risk matrix gives a clear picture of risky operations and helps organisations to implement response measures, optimising the risks. The proposed methodology is tested in a specific organisation. The study uses the methods of systematic approach, analysis and synthesis, abstraction and generalisation.